Frontispiece: PSYCHE Pure Shift NMR Spectroscopy. Issue 53 (21st September 2018) - Foroozandeh, Mohammadali; Morris, Gareth A.; Nilsson, Mathias
Abstract : The PSYCHE method is one of the most recent broadband homonuclear decoupling or "pure shift" NMR techniques, and is rapidly becoming exploited by chemists in academia and industry. Although it is quite user‐friendly and easy to implement, PSYCHE has so far remained one of the more mysterious and less well understood of NMR techniques. Herein some insights into the theory and practice of PSYCHE pure shift NMR spectroscopy is offered to the readership with an introduction to some new experimental frameworks that will help end users to exploit its full potential, see Concept by M. Nilsson et al. onpage 13988 ff.